Victorian Bloomsbury - Rosenbaum, S.P. author. aut Link
XVI, 316 p.
Keywords: 'A subtle and powerful picture of the Bloomsbury Group...S P Rosenbaum is an unparalleled interpreter of the philosophical as well as the literary traditions absorbed by this group.' Richard Ellman 'This is more detailed, more considered, more extensive, and therefore far more valuable than anything of the kind we have had before...required reading for anyone professing a serious interest in Bloomsbury.' Andrew McNellie This first volume of a three-volume study of the early literary history of the Bloomsbury Group describes the intellectual, family and Cambridge backgrounds of Bloomsbury as they are reflected in the Group's early or autobiographical works. While many books have been written on the Bloomsbury Group this is the first to study comprehensively the literary history of their interrelated achievements. Professor Rosenbaum has written a wonderful account of the ideas and people who were the early influences on the Group. He sees the modern period not as the age of 'great men', but in a new light, where original ideas about art, women and society. This book will be of interest not only to anyone fascinated by the Bloomsbury Group, but also to students of Woolf or Forster or Keynes or Strachey who need to know the background of those writers.